PELATIHAN KARYA ILMIAH PADA BIDANG KIMIA BAGI SISWA SMA PGRI JAYAPURA - Diana M. Abulais; Septiani Mangiwa (LPPM Uncen, 2022)
Community service activities have been carried out at SMA PGRI Jayapura, Heram District, Jayapura City, Papua Province. The purpose of this service is to increase students' interest in chemistry through scientific papers training with simple research methods. The initial stage carried out in this activity is the socialization of scientific papers. The next stage is conducting simple research, processing data and training in writing scientific papers. The research topic chosen is the determination of water hardness by complexometry. During this activity the students were very enthusiastic and motivated. This can be seen when students listen to material explanations, discuss, conduct research and write reports. Based on the evaluation results, the success rate of this activity reached 80%. This is because there are still some students who have difficulty in processing data and writing reports. Therefore, the role of the teacher is very important in assisting students to increase interest and creativity in producing a scientific work.Keywords: training; scientific work; SMA PGRI Jayapura